Idiopathic Hypertrophic Pachymeningitis Presenting with Unilateral Diminution of Vision and Papilloedema - Namrata; Rahul Sidheshwar Ranjan; Ruchika Agarwal; Anil Kumar Singh; Kumar Varun (Delhi Journal of Ophthalmology)
Idiopathic hypertrophic pachymeningitis (IHP) is a rare condition characterized by a chronic fibrosing inflammatory process usually involving either the intracranial or spinal dura matter and rarely both. Neurological symptoms are mostly nonspecific. Patients commonly present with long-standing headache and/or progressive neurologic deficits, multiple cranial nerve palsies or blindness. In this case report, we present a case of IHP in a 19-year-old male with unilateral diminution of vision and papilledema due to the involvement of intracranial duramater.